2014
DOI: 10.18388/abp.2014_1937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of P1' substrate specificity of staphylococcal SplB protease.

Abstract: Staphylococcus aureus is a dangerous human pathogen characterized by growing antibiotic resistance. Virulence of S. aureus relies on a variety of secreted and cell surface associated virulence factors among which certain proteolytic enzymes play an important role. Amid staphylococcal extracellular proteases, those encoded by the spl operon remain poorly characterized, both in terms of enzymology and their physiological role. Initial data demonstrated that Spl proteases exhibit restricted substrate specificity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…We observed that SplB did not cleave the peptide, indicating that SplB recognition sites are distinct from the trypsin target site as seen for the neutrophil derived enzymes. It also signifies the specificity of SplB in choosing its substrate and fits the published preferred cleavage motifs of SplB, WELQ//Q, WELQ//N and WELQ//G (61,62).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We observed that SplB did not cleave the peptide, indicating that SplB recognition sites are distinct from the trypsin target site as seen for the neutrophil derived enzymes. It also signifies the specificity of SplB in choosing its substrate and fits the published preferred cleavage motifs of SplB, WELQ//Q, WELQ//N and WELQ//G (61,62).…”
Section: Discussionmentioning
confidence: 68%
“…We found that SplB did not cleave the peptide, indicating that SplB recognition sites are distinct from the trypsin target site as seen for the neutrophil derived enzymes. Previous studies characterizing SplB cleavage specificifity had identified preferred cleavage motifs of SplB as WELQ//Q, WELQ//N and WELQ//G (65, 66). While the entire SplB cleavage motif was not identified in the PAR2 N-terminus, a Q 27 //G cleavage site is present upstream of the trypsin cleavage site and needs to be investigated further in future studies as the putative SplB cleavage site on PAR2.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MgrA, SarR, and SaeR each bring about profound upregulation of the spl operon, to levels that rival and, in the case of SaeR, exceed, that of SarA and CodY for protease control. This is of interest because the Spls are well known for their narrow substrate specificity (5254). Indeed, these enzymes share strong homology and many enzymatic characteristics with the exfoliative toxins of S.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, MgrA, SarR and SaeR each bring about profound upregulation of the spl operon, to levels that rival and, in the case of SaeR, exceed that of SarA and CodY for protease control. This is of interest because the Spls are well known for their narrow substrate specificity [5860]. Indeed, these enzymes share strong homology and many enzymatic characteristics with the exfoliative toxins of S. aureus .…”
Section: Resultsmentioning
confidence: 99%